SUATU PERBANDINGAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL ORANG-ORANG BIASA DAN NOVEL GURU AINI KARYA ANDREA HIRATA - Nur Haliza Fitri; Yundi fitrah; Irma Suryani (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The purpose of this study is to describe the similarities and differences in the values ​​of character education in the novels Orang-Orang Ordinary by Andrea Hirata and Guru Aini Ordinary. The type of research used in this study is qualitative by using descriptive methods. The results of the study address character education in the novel ordinary people and the novel Guru Aini by Andrea Hirata including religious values, honesty, tolerance, discipline, hard work, independent democracy, curiosity, national spirit, love of the motherland, respect for achievement, friendship, peace-loving, fond of reading, social care, responsibility. While the similarities of the two novels are seen from the aspects or values ​​found as well as the description of the aspects found. Aspects of the values ​​of character education include: religious values, honesty, discipline, hard work, independence, love of the motherland, love of peace, social care and responsibility. As for the differences in the value of character education, namely several aspects or values ​​of character education in the Ordinary People novel, only 9 aspects are found, while in the Guru Aini novel, 16 aspects are found.